Aryl Triflates in Phosphorus-Directed Rhodium(III)-Catalyzed C–H Activation - Roger, Julien; Sire, Charline; Tsivery, Anthonia; Cattey, Hélène; Hierso, Jean-Cyrille (Synthesis, 2023)
Aryl triflates are selected as suitable electrophile coupling partners for the phosphorus-directed rhodium(III)-catalyzed direct C–H arylation of polyaromatic phosphines. We report herein simple conditions for the peri-C–H functionalization of polyarylphosphines, where a [Rh(III)Cl2Cp*]2 precatalyst is employed to provide a convenient access to polyarylated phosphines in up to 93% isolated yield. This synthetic approach tolerates a wide range of different aryl trifluoromethylsulfonate derivatives bearing either electron-donating (COMe, CN, CF3 or Cl) or electron-withdrawing substituents (Me, OMe) at the para-, meta- and ortho-positions, and includes bulky polyaromatic triflate substrates. We further describe access to a large class of polycyclic aromatic hydrocarbon phosphine ligands, their oxidized derivatives (i.e., their oxides and selenides), their coordination modes with Au(I) and Cu(I) coinage metal salts, and their use as efficient ligands for the atom-economic, gold-catalyzed oxidative cyclization of terminal alkynes with nitriles.
Keywords: arylation; catalysis; P-ligand directed C–H activation; rhodium; trifluoromethylsulfonates; oxazoles